DAMPAK PRESIDENTIAL THRESHOLD TERHADAP PERGANTIAN ANTAR WAKTU DI DAERAH - Harun Fadhli; Sarip Sarip; Nur Rahman (Jurnal De Jure Muhammadiyah Cirebon, 2020)
A very difficult choice when faced with the full rights and formal requirements that have been taken, must respect the legal consequences of the single supporting party. As conceptualized by Sebastian Harnich, he will describe the relationship between theatrical stages in giving a formal impression of extra politics in Cirebon Regency. Different things happened in Cirebon Regency when the PAW took place, where regarding the single party proposing it was very clear that it did not violate the law. However, the situation becomes different when political power is mobilized to strengthen regional power. So the authors are interested in studying the impact of the regent threshold in PAW practices that are different from other regions. Then the researchers conducted a study entitled "Impact of the Presidential Threshold on Regent Threshold in Cirebon Regency". Researchers use the footing of previous research to get novelty in research. As a basis for research, several previous studies are related or have something to do with the focus of the study. Political parties that carry in the process of changing between times for deputy regional heads must recommend cadres of candidates for deputy regents who have the appropriate capacity and capability to become candidates for regional leaders. It is not then that the origin of recommending a candidate for deputy regional head is only as an invalid from the applicable law. So that with the election of a qualified deputy head of the region, the welfare of the people in the region and development in the region itself can be independent and advanced. Keywords: Change between times, Politics, Legal consequences.